Inhibition of Soybean 15-Lipoxygenase and Human 5-Lipoxygenase by Extracts of Leaves, Stem Bark, Phenols and Catechols Isolated From Lithraea caustica (Anacardiaceae) - Muñoz-Ramírez, Alejandra; Mascayano-Collado, Carolina; Barriga, Andrés; Echeverría, Javier; Urzúa, Alejandro (Frontiers in Pharmacology, 2020)
Lithraea caustica (Molina) Hook. & Arn. (Anacardiaceae), common name Litre, is an evergreen endemic plant used in the Mapuche Chilean folk medicine. The stem juice of L. caustica mixed with Rubus ulmifolius (blackberry) is used to treat cough and the infusion of leaves is used in baths to treat joint inflammations. In this study, the activities of 3-n-alk(en)yl-catechols, obtained from the dichloromethane extract of the epicuticular compounds of fresh leaves (DCME), stem bark petroleum ether extract (PEE), fractions of phenols and phenol-acid compounds obtained from the methanolic extract of defatted leaves (MeOHE) and aqueous infusion (AE) from fresh leaves, were evaluated as in vitro inhibitors of soybean 15-lipoxygenase (15-sLOX) and human 5-lipoxygenase (5-hLOX), one of the inflammation pathways. The 3-n-alk(en)yl-catechols were characterized by GC-MS and 1D and 2D NMR analysis as mixtures of 3-[(10E)-pentadec-10’-en-1-yl]-catechol, 3-[(10Z)-pentadec-10’-en-1-yl]-catechol and 3-n-pentadecylcatechol. In addition, two fractions, obtained from MeOHE, were characterized by LC-ESI-MS/MS as complex mixtures of known acids and phenolic compounds. DCME, MeOHE and ethyl acetate extract (AcOEtE) extracts showed inhibition against 15-sLOX, and the AE of fresh leaves, showed the best inhibition against 5-hLOX. The mixture of 3-n-alk(en)yl-catechols showed inhibition of 15-sLOX and 5-hLOX. The compounds 3-[(10Z)-pentadec-10’-en-1-yl]-catechol (IC50 2.09 µM) and 3-n-pentadecylcatechol (IC50 2.74 µM) showed inhibition against 5-hLOX. The inhibition values obtained for the 3-n-alk(en)yl-catechols are in the range of well-known inhibitors of 5-hLOX. Acetylation of the 3-n-alk(en)yl-catechols blocks the inhibitory activity, indicating that the free catechol function is necessary for the enzyme inhibition. In addition, the fractions of phenols and phenol-acid compounds showed inhibitory activity against 15-sLOX and the AE, showed a good inhibition against 5-hLOX. These results would be in agreement with the use of L. caustica, as an anti-inflammatory in Mapuche ethnomedicine.